Rolled vs. ground grain for fattening yearling heifers. - Cox, R.F.; Smith, E.F. (Kansas Agricultural Experiment Station, 2012)
A great deal of interest in rolled grain has been expressed. Some commercial feeders have purchased rollers in preference to grinders; a few feeders truck grain to town to have it rolled in preference to grinding grain at home. The usual recommendation for grain preparation for fattening commercial cattle has been to have it cracked or medium ground, not finely ground. Rolled grain has been considered by most people to be equal to medium ground or cracked grain and by some to be superior to medium ground or cracked grain. No conclusive experimental evidence was available as to the best method of grain preparation for fattening cattle. The objective of this study then is to find out which is the best method of grain preparation: rolling, coarse grinding or fine grinding.
Keywords: Beef; Rolled vs. ground grain; Gain; Heifers